3-Cyclohexyl-1-(3,5-dinitrobenzoyl)thiourea - Saeed, Sohail (International Union of Crystallography, 2011)
The structure of the title thiourea derivative, C(14)H(16)N(4)O(5)S, features an almost planar central C(2)N(2)OS fragment (r.m.s. deviation = 0.005 Å), an arrangement stabilized by an intramolecular N—H⋯O hydrogen bond. The terminal rings are twisted out of this plane, the dihedral angle formed with the benzene ring being 33.22 (10)°. The cyclohexyl ring is disordered, with two orientations (50:50) being resolved. The mean plane passing through the atoms of each disordered component forms dihedral angles of 65.7 (2) and 82.4 (3)° with the central plane. Centrosymmetric dimers mediated by an eight-membered {⋯HNC=S}(2) synthon occur in the crystal.